HUBUNGAN PERAWATAN DENGAN KESEHATAN RAMBUT MAHASISWI YANG MENGGUNAKAN KERUDUNG DI JURUSAN KESEJAHTERAAN KELUARGA FAKULTAS TEKNIK UNIVERSITAS NEGERI PADANG - ARISANDI, DESSY; Rahmiati, Rahmiati; Yuliana, Yuliana (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2014)
This study aims to analyze the relationship between care with hair health of female colleger who wear veil in Family Welfare Department the Faculty of Engineering, State University of Padang. This study consists of two indicators such as hair care and hair health. This research is descriptive research that is correlational. Sampling technique in this study was done by using proportional random sampling as many as 66 person with female colleger as research subject who wear the veil in the Family Welfare Department, Faculty of Engineering, State University of Padang. Techniques of data collection was a questionnaire with Likert Scale and the Guttman Scale which tested for validity and reliability. Analysis using the percentage formula. The results showed that female colleger who wear the veil, hair care are generally classified as being performed by 73% while the percentage of hair health as very low with a percentage of 45%, no significant relationship exists but has a positive relationship between care with hair health.Keywords: Hair care, Hair Health, Female colleger, Veil